An Assessment of the Shortcomings of the Growth of the Capital Markets in Uganda. - Bertha Twesigye (Uganda Christian University, 2025)
This study examines the shortcomings of capital market growth in Uganda. The specific objectives were to identify the types of capital markets, assess the shortcomings of their growth, evaluate and critique the role of capital markets, and recommend steps and solutions to mitigate the challenges affecting capital markets. The study employs a desk review method, primarily focusing on secondary data collected, to analyze the legal, institutional, and socio-economic dimensions of the capital markets’ as regulated by the Capital Markets Authority. Additionally, the study examines the socioeconomic, cultural, and institutional factors that influence the implementation and outcomes of the Capital Markets Authority Act and provides recommendations for reform. The findings of this research are expected to provide valuable insights for policymakers, practitioners, and stakeholders, informing evidence-based policy formulation that aims to strengthen Uganda's capital markets.
Undergraduate